Collagen Kinase Receptors as Potential Therapeutic Targets in Metastatic Colon Cancer - Lafitte, Marie; Sirvent, Audrey; Roche, Serge (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) is one of the leading causes of tumor-related death worldwide. While surgery can cure patients with early stage CRC, the 5-year survival rate is only 10% for patients with metastatic disease. Therefore, new anti-metastatic therapies are needed for this cancer. Metastatic spread defines the dissemination of cancer cells with tumor-initiating capacities from the primary tumor and their colonization of distinct organs, mainly the liver, for secondary tumor formation. Although the underlying mechanisms are not fully understood, components of the tumor microenvironment have gained strong interest. Among the known metastatic-promoting factors, collagens are extracellular matrix components that are deposited within the tumor, the tumor microenvironment, and at metastatic site(s), and are recognized to play essential roles during metastasis development. Here, we review recent findings on the metastatic role of the collagen receptors Discoidin Domain Receptors 1 and 2 (DDR1 and DDR2) in CRC and discuss the therapeutic value of targeting these receptor tyrosine kinases in this cancer.